POTENTIAL FOR THE DEVELOPMENT OF PHOTO TOURISM IN THE AREA OF LAKE RESERVOIRS IN THE MUNICIPALITY OF SUBOTICA - Mijuk, Nenad (The Business of Tourism, 2024)
The municipality of Subotica, with its lake reservoirs such as Palićko, Ludaško, Treset, Majdan and Krvavo lake, represent an ideal destination for the development of photo tourism. With rich flora and fauna, as well as beautiful landscapes, the lake reservoirs offer ideal conditions for photo safari activities. This paper analyzes the current tourist offer, identifying deficiencies in infrastructure and promotion, as well as potential target groups. Also, the possibility of cooperation with local communities and nature conservation organizations is being explored, in order to develop a sustainable tourist offer. The conclusion suggests that a strategic approach to the development of photo tourism could significantly contribute to the preservation of natural resources, the improvement of the local economy and the strengthening of the tourist identity of the municipality of Subotica.